2020
DOI: 10.1128/jvi.01962-19
|View full text |Cite
|
Sign up to set email alerts
|

Albumin Enhances the Rate at Which Coxsackievirus B3 Strain 28 Converts to A-Particles

Abstract: Three strains of coxsackievirus B3 (CVB3) differ by single mutations in capsid protein VP1 or VP3 and also differ in stability at 37°C in tissue culture medium. Among these strains, the CVB3/28 parent strain has been found to be uniquely sensitive to a component in fetal bovine serum (FBS) identified as serum albumin. In cell culture medium, serum increased the rate of CVB3/28 conversion to noninfectious particles at least 2-fold. The effect showed a saturable dose response. Rates of conversion to noninfectiou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…In enteroviruses E1 and E12 and coxsackievirus B3, serum albumin promotes virion expansion in a dose-dependent manner by sequestering the lipid factor from the VP1 hydrophobic pocket, as shown in in vitro experiments ( 6 , 20 , 21 ). Here, we studied and compared the roles of serum albumin and endosomal ion concentrations at neutral pH in triggering CVA9 expansion and genome release.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In enteroviruses E1 and E12 and coxsackievirus B3, serum albumin promotes virion expansion in a dose-dependent manner by sequestering the lipid factor from the VP1 hydrophobic pocket, as shown in in vitro experiments ( 6 , 20 , 21 ). Here, we studied and compared the roles of serum albumin and endosomal ion concentrations at neutral pH in triggering CVA9 expansion and genome release.…”
Section: Discussionmentioning
confidence: 86%
“…Despite extensive research, the physiological triggers leading to enterovirus uncoating after internalization, other than receptor binding and low pH in the endosomes, are poorly understood ( 19 ). Some studies have reported serum albumin as an uncoating cue for E1, E12, and coxsackievirus B3 ( 6 , 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…(A) CVB3 decay at 37°C when incubated with DMEM (slope= −0.06651; R2= 0.6940) or 10 8 of S. enterica (slope= 0.001960; R2= 0.9337). The first-order decay rate for CVB3 was determined by a best-fit line generated by fitted linear regression as previously described (48). (B) Rates of CVB3 Decay in either PBS or 10 8 CFUs of S. enterica .…”
Section: Resultsmentioning
confidence: 99%
“…In enteroviruses E1, E12 and coxsackievirus B3 serum albumin promotes virion expansion in a dosedependent manner by sequestering the lipid factor from the VP1 hydrophobic pocket as shown in in vitro experiments (6,20,21). Here we studied and compared the roles of serum albumin and endosomal ion concentrations at neutral pH in triggering CVA9 expansion and genome release.…”
Section: Discussionmentioning
confidence: 98%
“…Despite extensive research, the physiological triggers leading to enterovirus uncoating after internalization, other than receptor binding and low pH in the endosomes, are poorly understood (19). Some reports show serum albumin as an uncoating cue for E1, E12 and coxsackievirus B3 (6, 20, 21).…”
Section: Introductionmentioning
confidence: 99%